Grassland management in protected areas – implementaton of the EU biodiversity strategy in certain post-communist countries - Balázsi, Ágnes (Hacquetia, 2018)
The post-communist countries of Central-Eastern Europe (CEE) when implementing agricultural and conservation policies, face other challenges than Western European countries: (1) specifc institutional design for each, developed on the remnants of totalitarian system causing difculties for transposing directives; (2) diﬀerent integration of Natura 2000 network into national protected area governance resulting in slow elaboration of the management plans; (3) farming landscapes were better preserved than in Western Europe, but lacking the continuity of extensive farming so large areas of conservation; and (4) formal protection of sites, lacking in many cases fnancial support. Tis paper summarizes: the historical background of the last century that changed the farming landscapes of the CEE countries and the challenges in the management of protected areas in an unsteady socio-economic and political context. Te results are focusing on the Czech Republic, Slovakia, Hungary and Romania. Two main conclusions are proposed. First, socialism and capitalism slowly abolished family farming, causing people to become disconnected from the landscape – a key element in conservation oriented grassland management. Second, the gaps of knowledge on diﬀerent aspects of policy implementation sabotage the results of conservation initiatives.